Spatio-Temporal Patterns and Source-Dispersion Modeling Towards Sloth Bear–Human Conflict Management in Central India - Chaudhuri, Sankarshan; Bandyopadhyay, Meghna; Rajaraman, Rajasekar; Kalyanasundaram, Sankar; Sathyakumar, Sambandam; Krishnamurthy, Ramesh (Frontiers in Conservation Science, 2022)
Impact of humans on biodiversity in the form of spatially extensive occurrence of humans and subsequent habitat degradation lead to negative interactions between human and native wildlife. However, knowledge on spatial and temporal interface between human and wildlife is necessary to understand the root cause of such negative interactions, yet considerably understudied in the context of human-dominated landscape in south and south-eastern Asia. We took this opportunity, gaining insights on seasonal spatial interaction and spatio-temporal overlap between sloth bear (Melursus ursinus) and human and subsequently predict the conflict source sites and dispersion (i.e. hotspots) based on robust Geographic profiling (GP) method in Sanjay Tiger Reserve (STR), a human-dominated landscape of central India. Detection data of sloth bear and human were obtained from camera trap survey conducted for two years (2017-2018) and records of conflict incidents (2009-2019) were collected from forest department. We found that sloth bear can co-occur with humans independently irrespective of seasons, based on occupancy models. However, during summer, higher temporal overlap (Δ4 = 0.46) and lower spatial overlap (0.31) were observed between sloth bear and human. Contrastingly, lower temporal overlap (Δ4 = 0.29) and higher spatial overlap (0.44) were observed between the same, during winter. Activity patterns of sloth bear and human differed significantly with each other irrespective of seasons and also within same species in different seasons. Our findings indicated that significant changes in human activity especially during summer increased the likelihood of sloth bear-human interaction and subsequent conflict incidents. Mapping of conflict source and dispersion (with high accuracy) also predicted greater probability of conflict during summer, in compared to winter and thus presented successful application of GP models in this field. Also, camera trap data alone was able to predict the occurrence hotspots, demonstrating the use of camera trap records in successful prediction of source-dispersion of conflict. Present study would be useful for decision-makers to alleviate sloth bear-human conflict based on insights on seasonal variation of spatio-temporal overlap between the same and directing conservation efforts accordingly.